Air-permeable cellulosic triboelectric materials for self-powered healthcare products. (November 2022) - Fu, Qiu; Liu, Yanhua; Liu, Tao; Mo, Jilong; Zhang, Wanglin; Zhang, Song; Luo, Bin; Wang, Jinlong; Qin, Ying; Wang, Shuangfei; Nie, Shuangxi
Abstract: Wearable electronics with high-efficiency particulate matters (PMs) filtration and real-time respiratory monitoring offer everyone the opportunity to own a personal healthcare system. However, the power supply, breathability, and filtration performance of wearable electronics still have many challenges that need to be overcome. Herein, a self-powered air filter based on a respiration-driven triboelectric nanogenerator (R-TENG) was integrated with facemask for efficiently filtering submicron particles and respiration monitoring. The conductive cellulose aerogel/MOF composite, regarded as filtration and triboelectric material, was designed by in-situ and green synthesis method. The R-TENG was fabricated using conductive cellulose aerogel/MOF composite and polyvinylidene fluoride (PVDF) film as positive and negative triboelectric materials, respectively. Enabled by its desirable porous network structure and unique electricity generation feature, the air filter is capable of removing PM1.0 and PM0.5 and PM0.3 with high efficiency of 98.4 %, 97.3 % and 95.0 %, while maintaining a relatively low pressure drop of 86 Pa. Moreover, the air filter system can monitor breathing status without using an external power supply for disease prevention and medical diagnosis. This work designs a self-powered mask filter based on conductive cellulose aerogel/MOF composite with both PMs filtration and respiratory monitoring capabilities, which has excellent potential for air purification and healthcare applications. Graphical Abstract: ga1 Highlights: Conductive CA/Ni-HITP composite is prepared as filter media, triboelectric material and electrode. Portable self-powered air filter is constructed based on CA/Ni-HITP composite and PVDF membrane. The filtration efficiency for PM0.3, PM0.5 and PM1.0 are 95.0 %, 97.3 % and 98.4 % obtained by air filter. The self-powered air filter can also perform real-time breathing monitoring while filtering submicron particles.